Association of Serum and Fecal Bile Acid Patterns With Liver Fibrosis in Biopsy-Proven Nonalcoholic Fatty Liver Disease: An Observational Study. Issue 7 (26th July 2022) - Kasai, Yuki; Kessoku, Takaomi; Tanaka, Kosuke; Yamamoto, Atsushi; Takahashi, Kota; Kobayashi, Takashi; Iwaki, Michihiro; Ozaki, Anna; Nogami, Asako; Honda, Yasushi; Ogawa, Yuji; Kato, Shingo; et al.
Abstract : INTRODUCTION: No reports on both blood and fecal bile acids (BAs) in patients with nonalcoholic fatty liver disease (NAFLD) exist. We simultaneously assessed the serum and fecal BA patterns in healthy participants and those with NAFLD. METHODS: We collected stool samples from 287 participants from 5 hospitals in Japan (healthy control [HC]: n = 88; mild fibrosis: n = 104; and advanced fibrosis group: n = 95). Blood samples were collected and analyzed for serum BAs and 7α-hydroxy-4-cholesten-3-one (C4)—a surrogate marker for BA synthesis ability—from 141 patients. Concentrations of BAs, including cholic acid (CA), deoxycholic acid (DCA), chenodeoxycholic acid, ursodeoxycholic acid, and lithocholic acid (LCA), were measured using liquid chromatography-mass spectrometry. RESULTS: The total fecal BA concentration was significantly higher in the NAFLD group with worsening of fibrosis than in the HC group. Most of the fecal BAs were secondary and unconjugated. In the fecal BA fraction, CA, DCA, chenodeoxycholic acid, ursodeoxycholic acid, and LCA were significantly higher in the NAFLD than in the HC group. The total serum BA concentration was higher in the NAFLD group with worsening of fibrosis than in the HC group. In the serum BA fraction, CA, LCA, and C4 concentrations were significantly higher in the NAFLD than in the HC group. DISCUSSION: Fecal and serum BA and C4 concentrations were high in patients with NAFLD with worsening of fibrosis, suggesting involvement of abnormal BA metabolism in NAFLD with fibrosis progression. Abnormalities in BA metabolism may be a therapeutic target in NAFLD with fibrosis.